Pengaruh Waktu Pemberian dan Konsentrasi POC Kirinyuh (Choromolaena Odorata) Terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica Rapa L.) - Sari, Merdu; Saputra, Whin Themas Mico; Sukanto, Sukanto; Hairunnas, Hairunnas; Khadijah, Khadijah (Biram Samtani Sains, 2026)
This study aimed to determine the effect of application time and concentration of siam weed (Choromolaena odorata) liquid organic fertilizer (LOF) on changes and yields of plants bok coy (Brassica rapa L.), as well as their interaction. The research was conducted at the experimental farm of the faculty of agriculture, Gajah Putih University, pegasing subdistrict, central aceh regencey, from may to june 2025. The experiment used a factorial randomized block design (RBD) whith two trearment factors, namely the aplication time (W1= 5 and 10days after planting, W2= 10 and 15 days after planting, W3= 15 and 20 days after planting) and the concentraction of kirinyuh LOF (K1= 40 ml/L of water, K2= 80 ml/L of water, K3= 120 ml/L of water). Each combination was repeated three times, resulting in 27 experimental units